Detection of vortex charge and beam displacement by wavefront division interferometry - Chatterjee K.; Singh R.K.; Jha R. (My University, 2025)
In this work, a wavefront division interferometry method for determining the topological charge (l) of vortex beams (VB) is proposed and utilized for the detection of beam displacement. The method uses Fresnel biprism as a single element to determine vortex charge for up to l = ±10. Additionally, the interference pattern configuration is utilized to detect beam displacement in orthogonal directions. To accurately determine the shift in pattern due to beam displacement, a fringe scanning algorithm based on image correlation is proposed. The algorithm quantifies the fringe shift in terms of pixel units that is used to estimate the beam displacement. Sensitivity of 80 px/0.5 mm beam displacement along the x-direction is achieved with the system. The proposed method is single ended that can be integrated with optical assemblies for fast VB recognition. Furthermore, the displacement sensing utility could be used for precision alignment, propagation analysis, and monitoring physical fields. © 2023 Author(s).